Rapid Adaptation of Rat Brain and Liver Metabolism to a Ketogenic Diet: An Integrated Study Using 1H- and 13C-NMR Spectroscopy. Issue 7 (July 2015) - Roy, Maggie; Beauvieux, Marie-Christine; Naulin, Jérôme; Hamrani, Dounia El; Gallis, Jean-Louis; Cunnane, Stephen C; Bouzier-Sore, Anne-Karine
The ketogenic diet (KD) is an effective alternative treatment for refractory epilepsy in children, but the mechanisms by which it reduces seizures are poorly understood. To investigate how the KD modifies brain metabolism, we infused control (CT) and 7-day KD rats with either [1- 13 C]glucose (Glc) or [2, 4- 13 C2 ]β-hydroxybutyrate (β-HB). Specific enrichments of amino acids (AAs) measured by 1 H- and 13 C-NMR in total brain perchloric acid extracts were similar between CT and KD rats after [1- 13 C]Glc infusion whereas they were higher in KD rats after [2, 4- 13 C2 ]β-HB infusion. This suggests better metabolic efficiency of ketone body utilization on the KD. The relative rapid metabolic adaptation to the KD included (1) 11%-higher brain γ-amino butyric acid (GABA)/glutamate (Glu) ratio versus CT, (2) liver accumulation of the ketogenic branched-chain AAs (BCAAs) leucine (Leu) and isoleucine (ILeu), which were never detected in CT, and (3) higher brain Leu and ILeu contents. Since Glu and GABA are excitatory and inhibitory neurotransmitters, respectively, higher brain GABA/Glu ratio could contribute to the mechanism by which the KD reduces seizures in epilepsy. Increased BCAA on the KD may also contribute to better seizure control.